Quality Sorting and Trade: Firm-level Evidence for French Wine - Crozet, M.; Head, K.; Mayer, T. (Review of Economic Studies, 2012)
Empirical investigation of the quality interpretation of the Melitz (2003) model of firm heterogeneity and trade has been limited by the lack of direct data on quality. This paper matches firm-level export data with expert assessments of the quality of champagne producers to estimate the key parameters of that model. Quality monotonically increases firm-level prices, the probability of market entry, and export values. The estimated model—which calibrates the relative importance of firm-level quality and idiosyncratic demand—accurately predicts the average quality exported to each country. Simulations show that the data reject the polar alternatives where outcomes are based entirely on either quality or randomness.